Pemberian Pelatihan pada Kader Kesehatan tentang Pijat Oketani Guna Proses Kelancaran Pemberian ASI Ibu Menyusui - Ellyzabeth Sukmawati; Dahlia Arief Rantauni; Norif Didik Nur Imanah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
The purpose of implementing community service activities is to provide skills to health cadres about the Oketani massage technique as one of the techniques to facilitate the process of breast milk production. The method of implementing this service is carried out by providing training through lectures, discussions and questions and answers with the help of powerpoint media, mannequins and videos. The technique of measuring the achievement of the implementation of activities is carried out by measuring knowledge in pre and post test. The place where the service activities were carried out was carried out in Maos District, Cilacap Regency with a total of 50 health cadre participants with a time allocation from March to September 2024. The result of the activity was the Oketani massage training which is one of the alternatives for breastfeeding mothers to smooth the milk production process with massage techniques. The results of the pre-test and post-test assessments showed an increase in scores, which was an indicator of the success of this community service activity. The increase in knowledge of posyandu cadres is expected to be disseminated to the wider community, so as to have a wider positive impact. This activity has important implications in making a positive contribution to improving the knowledge of health cadres, which in turn can help solve maternal problems in terms of breastfeeding. Thus, this community service activity is not only beneficial for posyandu cadres, but also has the potential to improve the health of mothers and children in the community as a whole.